EFFECT OF WATERING FREQUENCY ON SEEDLING PRODUCTION OF PORANG (AMORPHOPHALLUS MUELLERI) FROM IN VITRO CULTURE IN A MIST BIOREACTOR - Althea Sandjaja, Nathan
Indonesia is a country with very diverse flora and fauna. However, Indonesia still faces issues related to food security, particularly regarding food safety. These problems arise from the reliance on rice as the primary staple food, which continues to experience annual declining production. The lack of diversification in staple food sources can be resolved by increasing the use of local foods as substitute staple foods, one of which is porang. Porang tubers have numerous advantages, including high mineral content, fiber, multifunctional glucomannan, and low calories and fat. However, conventional methods of propagating porang still face many challenges, especially in the provision of high-quality seeds. Therefore, in vitro culture methods using a mist bioreactor have been developed to produce highquality porang seeds in large quantities quickly. The aim of this research is to determine the effect of watering frequency on the production of porang (Amorphophallus muelleri) plantlets from in vitro culture in a mist bioreactor over 14 days. With watering variations of 2 minutes every 6 hours and every 18 hours, respectively, the porang culture experienced a relative seedling growth rate of 34.724 ± 2.714 mg/day and 41.371 ± 6.457 mg/day, a height increase rate of 0.191 ± 0.064 mm/day and 0.320 ± 0.170 mm/day, a shoot multiplication rate of 9.922 ± 0.647 shoots/explant/day and 7.883 ± 0.437 shoots/explant/day, changes in seedling chlorophyll content of 8.519 ± 0.088 SPAD units and 5.592 ± 0.201 SPAD units, seedling survival rates of 100% and 100%, changes in cultivation medium pH of 0.640 ± 0.272 and 0.650 ± 0.330, changes in cultivation medium sucrose content of 2.907 ± 1.757 g/L and 3.174 ± 1.598 g/L, changes in cultivation medium conductivity of 53.111 ± 8.468 µs/cm and 22.667 ± 4.163 µs/cm, carbon element bioconversion of 1.552 ± 0.075 g/L and 1.799 ± 0.112 g/L, oxygen element bioconversion of 0.633 ± 0.153 mg/L and 0.567 ± 0.058 mg/L, nitrogen element bioconversion of 0.028 ± 0.008% and 0.056 ± 0.011%, and the ratio between actual dry biomass weight and dry biomass weight from mass balance analysis of 131% and 142%